Utilization of Livestock Manure as Biogas and Liquid Organic Fertilizer (LOF) in Sumbermulyo Village, Pesanggaran, Banyuwangi - Masruri, Masruri; Wiryawan, Adam; Ikhtiarini, Nur; Setyawan, Hendrix Yulis; Hadiwijoyo, Erekso (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Biogas, generated by anaerobic bacteria breaking down organic matter, presents an energy alternative. Sumbermulyo, a Banyuwangi village, relies on dragon fruit farming and goat herding, facing shortages of subsidized urea fertilizer and LPG. The solution: utilizing goat manure for methane gas, replacing LPG. This community service project introduces a biogas processing pilot in Sumbermulyo, producing liquid organic fertilizer for local use. A fixed dome concrete biogas digester is constructed on a farmer group's land in 14 days, with peak pressure at 1.06 atm. Chemical analysis shows 0.032% N, 0.009% P, 0.144% K for the test digester, and 0.044% N, 0.005% P, 0.195% K for the reference digester, offering a sustainable energy and fertilizer solution for the community.